PENGARUH LITERASI KEUANGAN DAN RELIGIUITAS TERHADAP KEPUTUSAN MENGGUNAAN PRODUK BANK SYARIAH: 1. Kajian Teori , 2. Metode Penelitian, 3. Hasil dan Pembahasan , 4. Kesimpulan dan Saran, 5. Referensi - Sinta Purwanti; Iin Emy Prastiwi; Agus ` Marimin (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the influence of financial literacy and religiosity on people's decisions to use Islamic banking services. This study examines the influence of financial literacy partially, religiosity partially, and the influence of both simultaneously on the decision to use Islamic banking services. This study uses a quantitative approach through a survey data collection method. The research sample consisted of 100 respondents from the Kebayoran Lama Selatan District community. The number of respondents was determined using the Slovin formula. Data were obtained through a Likert scale questionnaire instrument and then analyzed using linear regression analysis. First, the data were confirmed for their feasibility through validity, reliability, and classical assumption tests. The results show that financial literacy and religiosity have a positive and significant impact on people's decisions to use Islamic banking services simultaneously (F = 138.482; sig = 0.000). The Adjusted R2 value shows 0.735, explaining that both variables are able to explain 73.5% of the variation in decisions, while the remainder is explained by other factors outside the research model. Partially, financial literacy has a positive and significant effect on the decision to use Islamic banking services (t=3.186; sig=0.002). Religiosity also has a positive and significant effect on people's decisions (t=13.469; sig=0.000). This indicates that religiosity dominates the influence on decisions.